2020
DOI: 10.1177/1096348020934849
|View full text |Cite
|
Sign up to set email alerts
|

Does Culture Affect Tourism Demand? A Global Perspective

Abstract: Tourism studies commonly focus on the determinants of tourism demand. While most examine factors such as economic determinants, research on the effect of culture on tourism demand remains underdeveloped. This study uses a Bayesian two-stage median regression method to eliminate the potential collinearity between cultural and travel distance and to estimate the impact of cultural distance more appropriately. The results show that while there is a negative relationship between cultural distance and tour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
0
11
1
Order By: Relevance
“…The impact of pandemics on tourism is not a new field of research (Liu et al, 2021). Several studies investigated the impact of epidemics such as Malaria, Ebola, Dengue, swine flu, avian flu, MERS, SARS and Yellow Fever on tourism and travel.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of pandemics on tourism is not a new field of research (Liu et al, 2021). Several studies investigated the impact of epidemics such as Malaria, Ebola, Dengue, swine flu, avian flu, MERS, SARS and Yellow Fever on tourism and travel.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, tourism demand modelling and forecasting have always been at the centre of tourism economics research (Dogru et al, 2021). Tourism demand forecasts directly affect destinations’ branding and marketing strategies (Liu et al, 2021). It guides the operational decisions of businesses in the tourism industry, such as pricing, personnel, capacity, resources and revenue management (Kulshrestha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Tourism demand explains the tangible and intangible set of goods and services consumed by tourists during their specific stays in the destination. Tourist arrivals, tourist expenditure, or tourist overnight stays are used mostly as dependent variables to explain tourism demand (Song et al, 2008;Rosselló-Nadal, HE, 2019;Khalid et al, 2020;Liu et al, 2021). Tourism determinants can be identified by the effect of economic and non-economic factors such as travel costs and income (Morley, 1992;Song et al, 2019;Inchausti-Sintes et al, 2021); relative price (Crouch, 1994;Morley, 1998;Permatasari, Esquivias, 2020;Ulucak et al, 2020); marketing expenditure (Crouch, 1995;Govers et al, 2007); cultural/natural heritage, political stability, governance quality (Cho, 2010;Tang, 2018;Detotto et al, 2021); terrorism, crime, and corruption (Poprawe, 2015;Saha, Yap, 2014;Fourie et al, 2020;Detotto et al, 2021); temperature and precipitation Qiang, 2020;Tang, Lau, 2021).…”
Section: Determinants Of Tourism Demand and Competitivenessmentioning
confidence: 99%
“…Hence, these significant economic effects have been widely investigated by researchers from different perspectives, such as promotion of local brands (Liu et al, 2021a), and changes in aesthetic information dissemination (Kim et al, 2019). With in-depth studies, researchers have identified the profound connotation of the rapid development of film-induced tourism: the extension of the immersive tourism (Marafa et al, 2020), the endowment of modern fashion labels for tourism destinations (Teng and Chen, 2020), and multi-dimensional integrations of modern media technology and traditional entertainment industry.…”
Section: Introductionmentioning
confidence: 99%